2012
DOI: 10.1103/physrevb.86.024108
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of thermally scattered electrons to atomic resolution elemental maps

Abstract: Electron energy-loss spectroscopy (EELS) and energy dispersive x-ray (EDX) analysis in scanning transmission electron microscopy (STEM) have the ability to produce elemental maps of a specimen at atomic resolution. In this paper we present EELS and EDX maps for the oxygen K-shell in 001 strontium titanate. The results initially seem to be anomalous since substantially more signal is obtained when the STEM probe is above the columns containing both titanium and oxygen than those containing only oxygen. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 19 publications
1
47
0
Order By: Relevance
“…. However, subsequent work has shown that the contribution of thermally scattered electrons can affect contrast in both EDS and EELS maps (Forbes et al, 2012), while studies of interfaces have revealed that the apparent atomic column size is affected by probe channeling, which directly depends on thickness (Lu et al, 2014(Lu et al, , 2013. Similar difficulties are encountered in STEM-EELS mapping, where image contrast reversals have been observed that are attributed to off-column channeling of the probe (Oxley et al, 2007, Wang et al, 2008.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…. However, subsequent work has shown that the contribution of thermally scattered electrons can affect contrast in both EDS and EELS maps (Forbes et al, 2012), while studies of interfaces have revealed that the apparent atomic column size is affected by probe channeling, which directly depends on thickness (Lu et al, 2014(Lu et al, , 2013. Similar difficulties are encountered in STEM-EELS mapping, where image contrast reversals have been observed that are attributed to off-column channeling of the probe (Oxley et al, 2007, Wang et al, 2008.…”
Section: Introductionmentioning
confidence: 79%
“…We find that the La L α signal is delocalized across the interface to Sr positions, as marked by the arrows in Figure 2(b); a similar, albeit much reduced, effect is seen for the B-sites. This delocalization and subsequent channeling to heavier sites can arise from both thermally and elastically scattered electrons, which are then able to go on to ionize other atoms (Forbes et al, 2012). As expected, delocalization results in a sizable increase in the apparent interface width, yielding: δ Sr = 0.54 ± 0.02, δ Ti = 0.26 ± 0.01, δ La = 0.60 ± 0.03, and δ Cr = 0.24 ± 0.01 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, counting statistics in X-ray analysis with typical setups will have significant disadvantages over EELS, but nevertheless, this will be very powerful for certain elements or combinations of elements, provided sufficient time is allowed for analysis. Atomic-resolution EDX has been demonstrated, [64][65][66] but there has been limited use of this to date for the study of functional oxides 67,68 and mostly focussed on the methodology and not on the science of the functional oxides.…”
Section: Basics Of Stemmentioning
confidence: 99%
“…This may include the combination of EELS, X-ray spectroscopy, 68 cathodoluminescence, 159,160 and secondary electrons 167 in order to provide a complete quantitative picture of the structure, chemistry and properties at the atomic or nanoscale.…”
Section: Future Directions In Aberration-corrected Stem Of Functionalmentioning
confidence: 99%
“…Improvedefficiency XEDS detectors have reduced the acquisition time and electron dose required for XEDS elemental mapping and thus enabled new possibilities for compositional mapping of nanomaterials (Fig. 1b) as well as atomic resolution elemental analysis (Kotula et al, 2012;Allen et al, 2012;Forbes et al, 2012).…”
mentioning
confidence: 99%